2018
DOI: 10.1002/pssr.201800176
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence Dynamics of Localized States in a Single GaAs/AlGaAs Quantum Ring

Abstract: Interferometric correlation spectroscopy is performed to investigate the decoherence dynamics of localized excited states in a single GaAs/AlGaAs quantum ring. For increasing temperature and excitation, we observe that the decay of interferometric envelope and the Fourier‐transformed spectrum remain exponential and Lorentzian, respectively. The linewidth broadening for temperature and excitation intensity can be attributed to enhanced acoustic phonon scattering and Auger scattering in the fast modulation limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the level spacing between the levels in QR is fine with sub-meV, and this causes various inelastic scattering. Recently, it has been found that the coherence time of a single QRs is under 30 ps [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the level spacing between the levels in QR is fine with sub-meV, and this causes various inelastic scattering. Recently, it has been found that the coherence time of a single QRs is under 30 ps [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding that the AB effect emerges in limited conditions of quantum coherence, this technique is of an importance for investigating the quantum coherence of an electron–hole pair rotating in a QR. So far coherent spectroscopy of QRs was barely studied …”
mentioning
confidence: 99%
“…However, recent work suggested that an internal scattering between the different vertical confinement states also contributes as an additional decoherence scattering. Regarding ≈25 ps of coherence time in localized excited states of a single GaAs/AlGaAs QR, we assumed T 2 = 10 ps for a wavefunction extended around the ring circumference. Consequently, while | P (3) ( t , τ )| 2 ∼ exp[−2 τ / T 2 ] decays for increasing τ (Figure (b)), the seven different states ( l = 0–6) contribute to oscillations in | P (3) ( t , τ )| 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation